Risk of Listeria monocytogenes ingestion in consuming coleslaw purchased from food vendors in the Accra metropolis - Dogbe, E.E. (University of Ghana, 2010)
It is very important that in managing food safety risks, the food, associated pathogen(s) and/or situations that lead to food borne illness are identified. It is also important to determine the magnitude of impact the risk has on public health (risk assessment). The microbial hazard Listeria monocytogenes has been associated with the vegetable cabbage (Brassica oleracea) and coleslaw an example of minimally processed vegetables with cabbage forming the predominant vegetable. This study was carried out to determine the prevalence and concentration of Listeria monocytogenes in fresh cabbage obtained from informal markets and commercially prepared ready-to-eat (RTE) coleslaw from food vendors in the Accra Metropolis. Detection and enumeration of L. monocytogenes was done using the 2009 edition of Health Protection Agency of Wales, UK standards for detection and enumeration of Listeria spp. To determine the magnitude of the impact of this hazard on public health, an exposure assessment through consumer survey was conducted with 300 vegetable consumers to determine how much (serving size) and how often (frequency/consumption rate) minimally processed vegetables such as coleslaw were consumed. Washing and/or decontamination of vegetables is an important step in managing the identified hazard (or risk). Thus the study determined the effectiveness of some common washing and decontamination methods on reducing the contamination level by Listeria monocytogenes in fresh cabbage. Results from the survey suggested that 55% of respondents consumed about one soup ladle (approximately 80g) of minimally processed vegetables including coleslaw on daily basis. Listeria monocytogenes was detected in 23 out of 24 samples of fresh cabbage (95.8% prevalence rate) obtained from informal markets and road side stalls. The prevalence rate for ready-to-eat coleslaw was 80.1%. Mean concentration of the pathogen in fresh cabbage was determined to be 29.79 ± 0.4 cfu/25g of fresh cabbage; RTE coleslaw had 25.51 ± 0.5 cfu/25g of RTE coleslaw. Risk assessment was conducted using the probabilistic approach. Data obtained from the detection and enumeration analysis were fitted into the risk model together with certain factors that influence the food beginning from farm till it reached the consumer (farm-to-fork). Using Monte Carlo simulations, the risk of ingesting Listeria monocytogenes on consuming commercially prepared coleslaw obtained from food vendors in Accra Metropolis was estimated as 90%. Although some washing methods in terms of concentration of disinfectant, pH and temperature reduced contamination level by L. monocytogenes; log reductions were not statistically significant (P > 0.05). Contact time between cabbage and washing solution (irrespective of concentration of disinfectant, pH and temperature) significantly reduced (P = 0.044) contamination level by the hazard.